ANALISIS KESALAHAN BERBAHASA TATARAN MORFOLOGI PADA TEKS PIDATO BERBAHASA INDONESIA KARYA MAHASISWA TIONGKOK - Sanjaya, Angga Trio (MIMESIS, 2023)
Language errors occur because the speaker violates the grammatical rules being studied (breaches of code). There is an assumption that the cause of such errors is due to the influence of interlingual and intralingual factors, namely the presence of language contact and a high level of complexity of the target language. This problem underlies the conduct of research on the language process of Chinese students learning Indonesian in the 2022/2023 Gasal Semester Rhetoric course. Thus, this study aims to determine the form of errors in the language of morphology in speech texts as well as the causes of errors that occur. The research method used is a qualitative method with a descriptive approach. The collection uses the listening method with basic tapping techniques, note-taking techniques, and observation techniques. The data source consists of 22 of speech texts and 26 sample sentences. Based on the results of the study, it was found that (1) Affixation errors include: (a) Removal of affixes and (b) Improper use of affixes; (2) The cause of language errors is due to the influence of the learner's B1 (L1 dependent error) and other factors outside of B1 (L1 independent error), including (a) Interference or negative transfer; (b) Teaching techniques; (c) Bilingual age; (d) The sociolinguistic situation of the learner. Kesalahan berbahasa terjadi karena penutur melanggar kaidah tata bahasa yang sedang dipelajari (breaches of code). Ada anggapan bahwa penyebab kesalahan tersebut karena pengaruh faktor interlingual dan intralingual, yaitu adanya kontak bahasa dan tingkat kerumitan bahasa sasaran yang tinggi. Persoalan inilah yang mendasari dilaksanakan penelitian terhadap proses berbahasa mahasiswa Tiongkok pembelajar bahasa Indonesia dalam mata kuliah Retorika Semester Gasal Tahun 2022/2023. Dengan demikian, penelitian ini bertujuan untuk mengetahui bentuk kesalahan dalam berbahasa bidang morfologi pada teks pidato sekaligus penyebab kesalahan yang terjadi. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Pengumpulan data menggunakan metode simak dengan teknik dasar sadap dan teknik catat serta observasi. Sumber data berupa 22 kumpulan teks pidato dan 26 kalimat sampel. Berdasarkan hasil penelitian ditemukan (1) Kesalahan afiksasi meliputi: (a) Penghilangan afiks dan (b) Penggunaan afiks yang tidak tepat; (2) Penyebab kesalahan berbahasa karena pengaruh B1 pembelajar (L1 dependent error) dan faktor lain di luar B1 (L1 independent error), meliputi (a) Interferensi atau transfer negatif; (b) Teknik pengajaran; (c) Usia kedwibahasaan; (d) Situasi sosiolinguistik pembelajar.